Natural killer cell–derived extracellular vesicles in cancer therapy. (30th September 2020) - Farcas, Marius; Inngjerdingen, Marit
Abstract: Cancer is a major cause of death in the industrialized world. New therapies are constantly being developed in order to reduce morbidity and mortality. NK cell–based cellular therapies have shown effect against haematological malignancies, but it has been difficult to target solid tumours due to low NK cell infiltration of the tumour and efficient tumour evasion strategies. NK cells release extracellular vesicles that naturally contain cytolytic proteins and tumour‐targeting molecules. These vesicles can directly interact with and kill malignant cells, and their small size could allow more efficient extravasation into the tumour tissue. Extracellular vesicles are also less sensitive to the hostile tumour microenvironment compared to cells. Based on their features, NK cell–derived extracellular vesicles represent promising novel tools in oncology. In this review, we summarize the current available literature on NK cell–derived extracellular vesicles and discuss how they may be utilized in therapy for solid tumours.